Taxonomic notes on Pertyella Mickel, 1952 (Hymenoptera; Mutillidae): - Roberto Alejandro Cambra; Kevin A. Williams; Ramon L. Ramos; Pedro R. Bartholomay; Matheus E. Trindade-Santos; Favízia F. de Oliveira (Revista Peruana de Biología)
The species formerly included in the Pertyella camposseabrai species-group are reviewed. The following two species are transferred from the genus Mutilla to Pertyella: P. angulosa (Burmeister, 1854) new combination, and P. carinigena (Cresson, 1902) new combination. The following new synonymies are proposed: P. mayri (Kohl, 1882); P. paulista Casal, 1964; P. viuva Casal, 1964; P. itinga Casal, 1964; P. camposseabrai Casal, 1964; P. uzai Fritz, 1990 and P. diasi Fritz, 1990 are jr. synonyms of P. angulosa; P. lenti Casal, 1964 is a jr. synonym of P. carinigena; P. aguaz Fritz, 1990 is a jr. synonym of P. cordoi Fritz, 1990. A new species in this group, Pertyella quirosae sp. nov., is described. Most characters that were formerly used to define this species-group are not consistent or exclusive to the group. Because the diagnostic features and component species in this species-group were changed, and because an older name is now available, this group of species is now called the P. angulosa species-group. Females of this group can be recognized by having the mesosoma with lateral stripes of dense silvery or whitish setae. A key to the species of the P. angulosa species-group and new distribution records are provided.